Degradation of pyrene, benz[a]anthracene, and benzo[a]pyrene by Mycobacterium sp. strain RJGII-135, isolated from a former coal gasification site. - Schneider, J (1996)
The degradation of three polycyclic aromatic hydrocarbons (PAH), pyrene (PYR), benz[a]anthracene (BAA), and benzo[a]pyrene (BaP), by Mycobacterium sp. strain RJGII-135 was studied. The bacterium was isolated from an abandoned coal gasification site soil by analog enrichment techniques and found to mineralize [14C]PYR. Further degradation studies with PYR showed three metabolites formed by Mycobacterium sp. strain RJGII-135, including 4,5-phenanthrene-dicarboxylic acid not previously isolated, 4-phenanthrene-carboxylic acid, and 4,5-pyrene-dihydrodiol. At least two dihydrodiols, 5,6-BAA-dihydrodiol and 10,11-BAA-dihydrodiol, were confirmed by high-resolution mass spectral and fluorescence analyses as products of the biodegradation of BAA by Mycobacterium sp. strain RJGII-135. Additionally, a cleavage product of BAA was also isolated. Mass spectra and fluorescence data support two different routes for the degradation of BaP by Mycobacterium sp. strain RJGII-135. The 7,8-BaP-dihydrodiol and three cleavage products of BaP, including 4,5-chrysene-dicarboxylic acid and a dihydro-pyrene-carboxylic acid metabolite, have been isolated and identified as degradation products formed by Mycobacterium sp. strain RJGII-135. These latter results represent the first example of the isolation of BaP ring fission products formed by a bacterial isolate. We propose that while this bacterium appears to attack only one site of the PYR molecule, it is capable of degrading different sites of the BAA and BaP molecules, and although the sites of attack may be different, the ability of this bacterium to degrade these PAH is well supported. The proposed pathways for biodegradation of these compounds by this Mycobacterium sp. strain RJGII-135 support the dioxygenase enzymatic processes reported previously for other bacteria. Microorganisms like Mycobacterium sp. strain RJGII-135 will be invaluable in attaining the goal of remediation of sites containing mixtures of these PAH.